2015
DOI: 10.1111/codi.13000
|View full text |Cite|
|
Sign up to set email alerts
|

Is there a limit to transanal endoscopic surgery? A comparative study between standard and technically challenging indications among 168 consecutive patients

Abstract: Transanal endoscopic surgery for rectal neoplasms appears to be safe and effective, even in patients presenting with a technically challenging tumours. Although the short- and long-term outcomes after TES are worse in patients with highly challenging tumours, nevertheless the technique should still be considered in patients at high risk of requiring a proctectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Operative mortality is less than 0.5%, and morbidity ranges from 4% to 30% in large series, depending on the inclusion of minor complications. 15-20 Our data are in line with these percentages. The most frequent complications include acute urinary retention (0% to 11%), bleeding requiring reoperation (0.7% to 9%), peritoneal entry (6% to 20%), and recto-vaginal fistula (0.3% to 1.4%).…”
Section: Discussionsupporting
confidence: 90%
“…Operative mortality is less than 0.5%, and morbidity ranges from 4% to 30% in large series, depending on the inclusion of minor complications. 15-20 Our data are in line with these percentages. The most frequent complications include acute urinary retention (0% to 11%), bleeding requiring reoperation (0.7% to 9%), peritoneal entry (6% to 20%), and recto-vaginal fistula (0.3% to 1.4%).…”
Section: Discussionsupporting
confidence: 90%
“…29 A recent retrospective review of a single institution's prospective database defined technically challenging lesions as those !5 cm in diameter, involving !50% of the lumen, or !10 cm from the anal verge. 58 These authors found that lesions possessing one of these technically challenging attributes had equivalent outcomes for many factors including local recurrence, but tumors with two or more of these attributes had significantly worse outcomes, including more local recurrence, peritoneal perforation, tumor fragmentation, rectal stenosis, and incomplete resection. As with many new surgical techniques, factors once thought to be absolute contraindications are rendered merely relative ones, based on experience and skill.…”
Section: Technical Issues Lesion Sitementioning
confidence: 99%
“…One of the complications of transanal surgery, including TAMIS, is potential abdominal entry, particularly for higher rectal lesions located above the peritoneal reflection [ 5 ]. If this occurs, simple transanal repair through the TAMIS platform can initially be attempted by suturing.…”
Section: Introductionmentioning
confidence: 99%